CONTINUITY OF CARE OF MRS. M WITH PERINEAL RUPTURE TITLE II AT PRATAMA NIAR CLINIC, MEDAN AMPLAS DISTRICT, MEDAN CITY IN 2025 - Gulo, Wini Sukariang Wati; Siti Nurmawan Sinaga; Rumondang; Misna Andriani; Melisda Nainggolan; Sariati; Aufa Risna Ayumahara, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Perineal rupture is one of the common complications of childbirth that may cause bleeding and infection if not properly managed. Continuity of care in midwifery is essential to ensure maternal and neonatal safety from pregnancy through family planning services. This article aims to describe the implementation of continuity of midwifery care for Mrs. M with a second-degree perineal rupture at Niar Primary Clinic, Medan City. This study employed a descriptive case study design using a continuity of care approach. The subject was Mrs. M, a 24-year-old woman (G3P2A0), who received comprehensive midwifery care starting from the third trimester of pregnancy, labor, postpartum period, newborn care, to family planning services. Data were collected through interviews, observations, physical examinations, and documentation. The results showed that maternal and fetal conditions during pregnancy were within normal limits. Labor occurred spontaneously through vaginal delivery with a second-degree perineal rupture, which was managed according to standard midwifery procedures. The postpartum period and newborn care proceeded without complications. The mother chose an appropriate postpartum family planning method. In conclusion, continuity of midwifery care was successfully implemented and contributed to optimal outcomes for both mother and baby.